2021
DOI: 10.3390/vaccines9070696
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Intention to Vaccinate against COVID-19 in the General Public in Hong Kong: Findings from a Population-Based, Cross-Sectional Survey

Abstract: Vaccination is one of the most effective ways to stop the spread of COVID-19. Understanding factors associated with intention to receive COVID-19 vaccines is the key to a successful vaccination programme. This cross-sectional study explored the rate of vaccination intention and identified its predictors using the health belief model (HBM) in the general population in Hong Kong during the pandemic. Data were collected between December 2020 and January 2021 via telephone surveys. Hierarchical logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
41
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 47 publications
(75 reference statements)
10
41
1
Order By: Relevance
“…In our study, vaccine acceptance in Model 3 (absent of Health Behavior Model variables) revealed that trust/satisfaction with authorities' ability to control COVID-19 transmission showed a two-fold increase in vaccine acceptance. This finding is congruent with previous research in Hong Kong, which found a three-fold increase in intentions to vaccinate [53]. In contrast to the Hong Kong study, we found public trust/satisfaction was no longer associated with vaccine acceptance in fully adjusted models.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study, vaccine acceptance in Model 3 (absent of Health Behavior Model variables) revealed that trust/satisfaction with authorities' ability to control COVID-19 transmission showed a two-fold increase in vaccine acceptance. This finding is congruent with previous research in Hong Kong, which found a three-fold increase in intentions to vaccinate [53]. In contrast to the Hong Kong study, we found public trust/satisfaction was no longer associated with vaccine acceptance in fully adjusted models.…”
Section: Discussionsupporting
confidence: 87%
“…The majority of the vaccine acceptance group expressed that the vaccine would defend against COVID-19 infection and would control or stop viral transmission [19,52]. According to Yan et al, the low tendency to accept vaccines has been consistent in Hong Kong across time [53]. Most of the people in the aforementioned studies were doubtful about the trust, safety, and effectiveness of the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study on the general population of Saudi Arabia also reported that participants who were concerned about becoming infected were 2.13 times more likely to take the vaccine [ 15 ]. In conformity with our results, studies based on the Health Belief Model have suggested that being male, older in age, perceived severity of COVID-19, perceived susceptibility, compliance with preventive guidelines, etc., were associated with greater intention to vaccinate [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A telephone-based survey conducted during December 2020-January 2021 and involving 1255 adults indicated that COVID-19 vaccine acceptance rate was 42%. 59 Another study involving two surveys among the same 2047 participants during the first and third waves of the local epidemic showed a declining rate for COVID-19 vaccine acceptance from 44.2% in February 2020 to 34.8% in August/ September 2020. 60…”
Section: Hong Kongmentioning
confidence: 99%